Programmed Cell Death Protein 1/Programmed Cell Death Protein Ligand 1 Immunosuppressants in Advanced Non-Small Cell Lung Cancer Research Progress in Treatment - Feng Li; Feng Li; Binchi Liao; Ting Wang; Tingting Qi; Yixin Wang (Frontiers Media S.A., 2022)
PD-1/PD-L1 play key roles in tumor immune escape and the formation of the tumor microenvironment, and are closely related to the generation and development of tumors. Blocking the PD-1/PD-L1 pathway can reshape the tumor microenvironment or block the formation of the tumor microenvironment and enhance endogenous antitumor immune response. Clinical trials show that the treatment of non-small cell lung cancer (NSCLC) with PD-1/PD-L1 inhibitors has significant advantages. The review briefly describes these basic principles of the PD-1/PD-L1 pathway and action mechanism in the treatment of NSCLC. A summary of global PD-1/PD-L1 clinical trials and five PD-1/PD-L1 inhibitors approved by FDA, EMA and NMPA for advanced NSCLC were analyzed.